Distinct Roles of Wnt/β-Catenin Signaling in the Pathogenesis of Chronic Obstructive Pulmonary Disease and Idiopathic Pulmonary Fibrosis - Juan Shi; Feng Li; Meihui Luo; Jun Wei; Xiaoming Liu (Hindawi Limited, 2017)
Wnt signaling pathways are tightly controlled under a physiological condition, under which they play key roles in many biological functions, including cell fate specification and tissue regeneration. Increasing lines of evidence recently demonstrated that a dysregulated activation of Wnt signaling, particularly the Wnt/β-catenin signaling, was involved in the pathogenesis of chronic pulmonary diseases, such as chronic obstructive pulmonary disease (COPD) and idiopathic pulmonary fibrosis (IPF). In this respect, Wnt signaling interacts with other cellular signaling pathways to regulate the initiation and pathogenic procedures of airway inflammation and remodeling, pulmonary myofibroblast proliferation, epithelial-to-mesenchymal transition (EMT), and development of emphysema. Intriguingly, Wnt/β-catenin signaling is activated in IPF; an inhibition of this signaling leads to an alleviation of pulmonary inflammation and fibrosis in experimental models. Conversely, Wnt/β-catenin signaling is inactivated in COPD tissues, and its reactivation results in an amelioration of airspace enlargement with a restored alveolar epithelial structure and function in emphysema models. These studies thus imply distinct mechanisms of Wnt/β-catenin signaling in the pathogenesis of these two chronic pulmonary diseases, indicating potential targets for COPD and IPF treatments. This review article aims to summarize the involvement and pathogenic roles of Wnt signaling pathways in the COPD and IPF, with a focus on the implication of Wnt/β-catenin signaling as underlying mechanisms and therapeutic targets in these two incurable diseases.